Pemikiran Politik Al-Farabi - Sa’adi, Gusti Muslihuddin; Hasan, Ahmadi; Umar, Masyithah; Khasyi'in, Nuril (PT. Sharia Journal and Education Center, 2024)
Abstract Al-Farabi, a renowned philosopher of the medieval period, contributed significantly to political thought with his concepts on the ideal state, which he termed